2015
DOI: 10.1055/s-0034-1398487
|View full text |Cite
|
Sign up to set email alerts
|

De Quervain Tenosynovitis Following Trapeziometacarpal Ball-and-Socket Joint Replacement

Abstract: Osteoarthritis at the base of the thumb can cause severe pain, weakness, and deformity and can result in marked disability. Shear stress forces, due to weakening of the palmar beak ligament, can cause damage to the articular cartilage that can progress to degenerative osteoarthritis. 1 Initially, osteoarthritis of the trapeziometacarpal (TMC) joint should be treated conservatively. Surgery has been suggested in cases of pain that hampers the activities of daily life. In one study, patients treated conservative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
2
16
2
Order By: Relevance
“…(2013) also reported good outcomes, no dislocations and only one revision due to polythene wear in a prospective study of 22 patients. In another study by the same authors, Goubau et al. (2015) reported 17% of De Quervain tenosynovitis within the first postoperative year.…”
Section: Discussionmentioning
confidence: 87%
“…(2013) also reported good outcomes, no dislocations and only one revision due to polythene wear in a prospective study of 22 patients. In another study by the same authors, Goubau et al. (2015) reported 17% of De Quervain tenosynovitis within the first postoperative year.…”
Section: Discussionmentioning
confidence: 87%
“…The Goubau et al study [29] also reported a 17% rate of De Quervain's tenosynovitis. These complications generally occur around the 3rd month and although not very serious, they delay functional recovery.…”
Section: Tendinopathymentioning
confidence: 89%
“…De Quervain's tenosynovitis occurs when patients resume their activities and use their hand more. The alignment of the thumb column, its lengthening (increased postoperative scaphometacarpal index) [29] and the increased tension on tendon structures may have caused of these tenosynovitis cases.…”
Section: Tendinopathymentioning
confidence: 99%
“…Side effects such as trigger thumb or de Quervain's disease were also mentioned in other surgical procedures. 24 We think that one reason could be the restricted movement postoperatively due to wearing a thumb orthosis for 4 weeks. Therefore, we shortened this postoperative treatment to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%